Use of allied‐health services and medication among adults with ASD in Latin America. Issue 10 (2nd August 2021) - Torres, Andy; Lecusay, Denise; Valdez, Daniel; Rosoli, Analía; Garrido, Gabriela; Cukier, Sebastián; Paula, Cristiane Silvestre; Garcia, Ricardo; Rattazzi, Alexia; Montiel‐Nava, Cecilia
Abstract: ASD is a neurodevelopmental disorder that affects people across the entire lifespan, yet most of the research identifying the health and medical needs for autistic individuals have been among minors. As individuals with ASD transition to emerging adulthood, the services, already limited, become less available. This study aimed to identify the use of services for Latin American adults on the spectrum. We surveyed 295 caregivers of adults with ASD from six Latin American countries. Comparing the results for all the possible services observed in this study, the adults in our sample were primarily underserved: 84.4%–95.9% were receiving zero hours per week, 3.7%–12.9% 1%–10 h, 0%–1.7% 11–20, and only 0%–1% above 20 h of services. Almost half of the sample used medication, and neurologists were the most consulted health providers. Next to inexistent health care usage in Latin American adults with ASD highlights socioeconomic and health disparities in service provision for ASD in the region. The lack of services places adults with ASD in Latin America at a higher risk of worse symptom severity than autistic adults from regions with broader access to services. Lay Summary: This study aimed to identify the quantity of services received by adults with autism in Latin America. Most of our sample was not receiving health services yet almost half had access to medication. This could mean that adults with autism in Latin America are at higher risk for poorer health.